REGIONAL FEATURES AND PROBLEMS OF RURAL POPULATION AGE STRUCTURE IN THE RA FRONTIER AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The RA frontier settlements are primarily villages and among the other factors, their perspective development depends on the population number of settlements and age structure of population as well. Based on the analysis and generalization of factual and statistical data, the regional differences of the rural population age structure of the RA frontier areas are given in the article. The current problems have been revealed.
Keywords: frontier areas; frontier settlements; population age structure; main age groups; settlements population number; problems